A STUDY ON THE EPIDEMIOLOGICAL PROFILE OF ACUTE DRUG POISONING CASES ADMITTED TO OUR HOSPITAL (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Acute drug poisoning is a major public health problem and one of the most common medical emergencies encountered in hospitals. It contributes significantly to morbidity and mortality, particularly among young adults. The pattern of poisoning varies depending on the availability of drugs, socioeconomic factors, and regional prescribing practices. Understanding the epidemiological profile of acute drug poisoning is essential for early diagnosis, effective management, and prevention strategies. Methodology: This hospital-based observational study was conducted in the Department of Emergency Medicine at from May 2025 to February 2026. A total of 40 patients above 18 years of age admitted with a history of acute drug poisoning were included in the study after obtaining informed consent. Patients with multiple modes of poisoning and those who did not provide consent were excluded. Detailed clinical history, demographic profile, type of drug consumed, duration since consumption, symptoms, clinical findings, and outcomes were recorded using a structured proforma. Data were analyzed using descriptive and inferential statistical methods. Results: The mean age of the study participants was 37.36 ± 41 years, with the majority belonging to the 31–40 years age group. Most participants reached the hospital within 7–24 hours following drug consumption, with a mean duration of 11.67 ± 5.15 hours. Benzodiazepines were the most commonly consumed drugs (17.5%), followed by NSAIDs (12.5%) and antihypertensive medications (10%). Vomiting was the most common presenting symptom observed in 35% of participants, followed by giddiness (32.5%), abdominal pain (17.5%), and altered sensorium (15%). Conclusion: Acute drug poisoning predominantly affects young and middle-aged adults, with benzodiazepines and NSAIDs being the most frequently implicated agents. Early hospital presentation and prompt management play an important role in reducing complications. Public awareness regarding safe drug usage, mental health counseling, and regulation of medication accessibility are essential to reduce the burden of acute drug poisoning.